Networking in the osteoarthritis research community in the digital era - Rachel K. Nelligan; Anca Maglaviceanu; Jocelyn Bowden; Jackie L. Whittaker; Tobias Winkler; Jos Runnhar; Mohit Kapoor; Chunyi Wen (Osteoarthritis and Cartilage Open, 2025)
Networking is a vital skill for osteoarthritis (OA) researchers, offering pathways to collaboration, visibility, and career development. Recognising the evolving nature of networking in the digital era, the OARSI Early Career Investigator (ECI) Committee hosted a workshop at the 2025 OARSI World Congress titled “Navigating Networking: Strategies for Connecting Across Cultures and Personalities.” This editorial summarises key insights from the session’s expert presentations and panel discussion. Dr Jocelyn Bowden highlighted the enduring value of face-to-face networking for rapport-building, encouraging ECIs to approach interactions with curiosity and preparation. Dr Jackie Whittaker explored virtual networking and personality-based strategies, noting that aligning communication methods with individual preferences can enhance engagement. She stressed that there is no one-size-fits-all approach. Professor Tobias Winkler provided guidance on industry networking, underscoring the importance of understanding corporate decision-making processes and collaboration dynamics. The session closed with reflections on cultural competence and the role of authenticity in communication. While digital tools may support networking, the speakers agreed that genuine, personalised interactions remain essential. Across all formats, researchers were encouraged to build inclusive, diverse networks grounded in sincerity and mutual respect. For those unable to attend, this summary offers practical strategies to support effective networking across platforms, cultures, and career stages.